Convergent nanotechnologies - Kolisnychenko, Stanislav (Advanced materials research, 2015)
As an integral part of the NBIC technologies paradigm, nanotechnologies in their turn are rather convergent. Convergence of nanotechnologies leads to creation of new materials and technologies which are needed in almost all fields of human activity. A vivid example of the convergence of nanotechnology is this collection of papers, which includes materials of scientific and experimental research from different disciplines, but which are united by one concept -convergent nanotechnologies.